A realidade sacramental da liturgia à luz do realismo zubiriano: análise da atualidade de Cristo, de sua morte e ressurreição, na celebração dos sacramentos e na vida - Neves, Marcos Vieira das (2023)
This research on the sacramental reality of the Liturgy in the light of the Zubirian realism: analysis of Christ’s actuality, of his death and resurrection in the celebration of the Sacraments and in life, aims to approach the Liturgy as reality in which the actions of Christ are actualized as much in the celebration of the Sacraments as in Christian life. Such research justifies itself because, beyond starting from the theological comprehension of Liturgy of the II. Vatican Council shows it as actualization of Christ’s actions, not a simple sign that points to another reality; liturgical actions are real and incorporate man into Christ, make of him a Christian, “another christ” in the world. Assuming as theoretic and methodologic foundation the analysis of Zubiri’s works, especially the Trilogy of Sentient Intelligence and the theologal Trilogy, and of his various commentators, we present the hypothesis from his thought that the sacramental reality of Liturgy is precisely sacramental because it does not point arbitrarily to something else, mas it is action of Christ himself, especially his supreme action, his Passover. As results, we verify that the Zubirian realism provides an invaluable theoretic background to actual theological reflection and offers advance to liturgical Theology. The framework given by his Philosophy allows to think man and the sacramental reality of Liturgy from the structural unity of feeling and thinking, of man’s in se and his being in the world directly related to real things of the world. So, acting, thinking, judging, and reflecting the sacramental reality of Liturgy show Christ’s reality itself, actualized to man and to the world. In this sense, Zubirian thought enriches the notion of sacramentality given by the Council and illuminates a new way to contemplate the Liturgy: God actualizes himself in the liturgical actions and, therefore, salvation in the Liturgy is real. As privileged locus, in which man experiences his reconnexion to the foundation of reality, to God, in the Liturgy the plasmation of man in Christ is real. At last, we verify a importance of our research on the sacramental reality of Liturgy in the light of Zubirian realism inside Francis’ Ecclesiological itinerary; for that we resume some elements of “Francis’ Church” to enter into dialogue with Zubirian thought. So, we verify how much his Philosophy may contribute to the advance of liturgical Theology in a “Church which goes forth”. By the sacramental reality of Liturgy, from Zubirian realism understood, man is reconnected to God, plasmed into Christ, made “other christ”, finally, dei-formed